DAMPAK COVID-19 TERHADAP IMPLEMENTASI PELAJARAN DI SEKOLAH DASAR KRISTEN EFATA DESA BAMBUNG KECAMATAN GEMEH KABUPATEN KEPULAUAN TALAUD - TUWONE, MALDEN; KIYAI, BURHANUDDIN; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2021)
The purpose of this study was to determine the impact of Covid 19 in the implementation of learningat the Efata Christian Elementary School, Bambung Village, Gemeh District, Talaud IslandsRegency. This study used a qualitative research method. In order to obtain accurate, relevant, andaccountable data, the authors use several techniques in data collection, namely through observation,interviews and documentation. The data are then grouped to make it easier to filter which data areneeded and which are not. After grouping, the data is described by the author in the form of text tomake it more understandable. After that, the authors draw conclusions from the data, so that theycan answer the main research problem. From the results of the study, it was found that the impact ofCovid 19 in the implementation of learning at the Efata Christian Elementary School, BambungVillage, Gemeh District, Talaud Islands Regency occurred in the aspect of the impact on publicproblems, especially in the target group, the impact of direct costs incurred to finance the programand indirect impacts incurred as a result of implementation of the Covid 19 handling protocol policy.Keywords: Impact, Covid 19, Learning, School